FAKTOR-FAKTOR YANG MEMPENGARUHI KESADARAN MEREK, PERSEPSI KUALITAS DAN CITRA MEREK TERHADAP KETERIKATAN DESTINASI DENGAN LOYALITAS MEREK SEBAGAI VARIABEL INTERVENING PADA SOLO GREAT SALE - Nabiilah Aprilia Az-zahra; Soepatini Soepatini (JURNAL ILMIAH EDUNOMIKA, 2024)
Research on the factors that influence the influence of brand awareness, perceived quality, and brand image on attachment to festival destinations with brand loyalty as an intervening variable at Solo Great Sale can provide a clear picture of the factors that influence consumer interest in returning to visit the festival. The research approach used in this research is quantitative research. Hair et al. (2012) recommend the minimum number of research samples between five and ten times the number of variables or indicators of the questions being studied. In this study, there are 29 indicators so the recommended sample size is around 290. To mitigate the potential for invalid questionnaires, or in case of constraints, this study expanded the sample size to 313 participants. Data was collected via Google Form in questionnaire format, and there were a total of 313 responses. The results of the analysis show that brand awareness, perceived quality, and brand image have a positive and significant effect on brand loyalty at Solo Great Sale. Brand awareness and perceived quality have a positive and significant effect on destination attachment at Solo Great Sale.Brand image and brand loyalty have no positive and significant effect on destination attachment at Solo Great Sale.Brand awareness, perceived quality, and brand image have no positive and significant effect on destination attachment with brand loyalty as an intervening variable. Key words: Brand awareness, Perceived quality, Brand image, Brand loyalty, Destination attachment, Festival